2007
DOI: 10.1111/j.1740-8261.2007.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Heart Size in Retired Racing Greyhounds

Abstract: The vertebral heart size (VHS) is used to objectively assess cardiac dimensions on thoracic radiographs. A high VHS suggest the presence of cardiac pathology, such as dilated cardiomyopathy, degenerative atrioventricular valvular disease, pericardial effusion, pericardioperitoneal diaphragmatic hernia, tricuspid dysplasia, ventricular septal defect, or patent ductus arteriosus, among others. However, breed or body conformation can influence the VHS. Because Greyhounds have a high prevalence of physiologic syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 13 publications
2
58
2
4
Order By: Relevance
“…The mean VHS of all groups of dogs in the present study was greater than the upper limit for nor- mal heart size in most canine breeds (VHS ≤ 10.5) [6]. Values of VHS higher than the above upper limit have been reported for boxers (11.6 ± 0.8), cavalier king Charles spaniels (10.6 ± 0.5), Labrador retrievers (10.8 ± 0.6), whippets (11.0 ± 0.5) and greyhounds (10.5 ± 0.1) [4,15,20], but no boxers, cavalier king Charles spaniels, Labrador retrievers, whippets or greyhounds were included in the present study. The mean VHS of our dogs with cardiac or mixed origin of cough was significantly higher compared with the mean VHS of the dogs with a non-cardiac origin of cough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean VHS of all groups of dogs in the present study was greater than the upper limit for nor- mal heart size in most canine breeds (VHS ≤ 10.5) [6]. Values of VHS higher than the above upper limit have been reported for boxers (11.6 ± 0.8), cavalier king Charles spaniels (10.6 ± 0.5), Labrador retrievers (10.8 ± 0.6), whippets (11.0 ± 0.5) and greyhounds (10.5 ± 0.1) [4,15,20], but no boxers, cavalier king Charles spaniels, Labrador retrievers, whippets or greyhounds were included in the present study. The mean VHS of our dogs with cardiac or mixed origin of cough was significantly higher compared with the mean VHS of the dogs with a non-cardiac origin of cough.…”
Section: Discussionmentioning
confidence: 99%
“…The VHS is the vertebral scale sum of the long and short axes, each measured caudally from the cranial edge of the 4th thoracic vertebra. Normal VHS values have been established for cats [16] and ferrets [26] as well as for different canine breeds [4,15,20]. Furthermore, this method is largely employed for radiographic evaluation of the heart in dogs with different cardiovascular disorders.…”
mentioning
confidence: 99%
“…Research has demonstrated that Greyhounds have hematologic and biochemical differences from other breeds, some of which are not widely known in the veterinary field. [1][2][3] Greyhounds have physiologic differences including a larger heart size, 4,5 a higher vertebral heart score, 6 high glomerular filtration rate, 7 high arterial blood pressure, 4,5 and relative aortic stenosis. 8 To date, research has focused mainly on the physiologic and clinicopathologic peculiarities of Greyhounds, but there is little published data for disease prevalence in the breed.…”
mentioning
confidence: 99%
“…Şiddetli lordoz veya kifozu bulunan köpeklerde de VHS ölçümünün normalden yüksek çıkabileceği belirlenmiştir (8,12). Vücut kondisyon skoru ile VHS arasında Lhasa Apso ırkı dışındaki diğer köpek ırklarında herhangi bir anlamlı ilişki bulunmamıştır.…”
Section: Gerçekten Radyografik Kardiyomegali Var Mı?unclassified